2023
DOI: 10.1007/s00127-023-02443-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health First Aid crisis role-plays between pharmacists and simulated patients with lived experience: a thematic analysis of debrief

Abstract: Purpose Healthcare professionals, including pharmacists, can recognise and assist people experiencing mental health crises. Despite this, little is known about how pharmacists assist and engage with people presenting with signs and symptoms of mental health crises. This study aimed to (i) examine pharmacists’ mental health crisis assessment language during simulated patient role-plays (SPRPs) and (ii) explore participants’ experiences of participating in SPRPs of Mental Health First Aid (MHFA) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Encountering mental health crisis situations in a pharmacy can be a challenging experience for pharmacy staff; many express uncertainties about their level of training in how to initiate and conduct useful conversations that would not cause discomfort, further distress or harm amongst consumers [ 3 , 7 ]. As previously demonstrated with medical students practising clinical communication with SPs [ 25 ], the unexpected content of the SP scenarios in this study challenged students, however they were reflective of real-world experiences in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encountering mental health crisis situations in a pharmacy can be a challenging experience for pharmacy staff; many express uncertainties about their level of training in how to initiate and conduct useful conversations that would not cause discomfort, further distress or harm amongst consumers [ 3 , 7 ]. As previously demonstrated with medical students practising clinical communication with SPs [ 25 ], the unexpected content of the SP scenarios in this study challenged students, however they were reflective of real-world experiences in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…MHFA accreditation lasts 3 years; there is limited evidence to demonstrate the sustainability of improvements up to 6 months, and no studies have reported findings beyond 1 year post-MHFA training [ 14 , 22 ]. Longitudinal studies are needed to investigate whether MHFA-trained participants’ crisis assessment skills change over time [ 3 ], which may also be evaluated via SPs. It is also suggested that studies use a control or comparison group to test the independent impact of MHFA training and/or SP role-play assessments on intervention behaviours [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Debriefing sessions facilitate reflective thinking and offer constructive feedback, promoting a deeper understanding of the learning experience [ 41 ]. Moreover, using a safe learning environment encourages reflection and the application of mental health first-aid techniques [ 42 ]. Consequently, participants are empowered to analyze their actions, pinpoint areas for enhancement, and comprehend the potential impact of their interventions in real-world situations.…”
Section: Methodsmentioning
confidence: 99%
“…Recruited pharmacies were randomised to either the Intervention Group (IG) or CG. Further information regarding the IG, including the PharMIbridge intervention and PharMIbridge training, has been described previously [19,[23][24][25]. Twenty-six pharmacies were randomised to the CG with 68 pharmacists attending the CG training, which included training on participant recruitment and study processes for the RCT, including consumer eligibility, informed consent and service documentation [25] and Mental Health First Aid (MHFA) [26].…”
Section: Methodsmentioning
confidence: 99%